Efficiency enhancement and cost reduction in cement clinker production: A comprehensive energy and exergy analysis of a rotary kiln in Turkey - Ozkan, Seren; Acarali, Nil (ELSEVIER, 2024)
Clinker production in the rotary kiln was one of the most energy-intensive processes in the cement industry. The application of exergy analysis to cement manufacturing increased system performance and positively affected production costs. In this study, the energy and exergy analysis of a rotary kiln used for clinker production in a cement factory in Turkey was evaluated. The capacity of the kiln was 2900 tonnes per day and the L/D (Length/ Diameter) ratio of the cement kiln was 14.4. The energy and exergy efficiency of the rotary kiln was calculated as 49 % and 37 % respectively. The calculations showed that the loss in the cement production process was at a substantial level. To reduce the unit cost and improve the cement kiln performance, it was necessary to carry out improvement studies specific to the cement kiln. It was critical for evaluation of the energy conversation in cement industry.
Keywords: Rotary kiln; Exergy; Cement; Energy; IMPROVEMENT; EMISSIONS; Thermodynamics; Energy & Fuels; Engineering; Mechanics